2015
DOI: 10.1038/onc.2014.443
|View full text |Cite
|
Sign up to set email alerts
|

A novel recurrent CHEK2 Y390C mutation identified in high-risk Chinese breast cancer patients impairs its activity and is associated with increased breast cancer risk

Abstract: Certain predisposition factors such as BRCA1/2 and CHEK2 mutations cause familial breast cancers that occur early. In China, breast cancers are diagnosed at relatively younger age, and higher percentage of patients are diagnosed before 40 years, than that in Caucasians. However, the prevalence for BRCA1/2 mutations and reported CHEK2 germline mutations is much lower or absent in Chinese population, arguing for the need to study other novel risk alleles among Chinese breast cancer patients. In this study, we se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 44 publications
0
25
0
Order By: Relevance
“…18,19 Of note, 1 of our cases with macro chromosomal deletion/duplication (Case 10) also has CHEK2 p.Y390C, a variant associated with lung cancer. 20 That patient is without malignancy and is the oldest onset in our cohort. No patients had malignant transformation.…”
Section: Discussionmentioning
confidence: 83%
“…18,19 Of note, 1 of our cases with macro chromosomal deletion/duplication (Case 10) also has CHEK2 p.Y390C, a variant associated with lung cancer. 20 That patient is without malignancy and is the oldest onset in our cohort. No patients had malignant transformation.…”
Section: Discussionmentioning
confidence: 83%
“…The most studied germline mutation, c.1100delC, significantly augments the risk of early-onset and familial BC 91 . Other mutations have been reported in very young Pakistani women (p.P92R, p.R406C, p.H371Y, and p.D438Y) 92,93 , and in Chinese very young women (1169A > G) 94 .…”
Section: Chek2mentioning
confidence: 99%
“…Our previous studies [ 7 – 9 ] have been carried out on multiple related genes of the DNA damage pathway, and we found that CHEK2 Y390C mutation inhibited the efficacy of CHEK2 in response to DNA damage agents, indicating Y390C mutation significantly impaired CHEK2 function during DNA damage response. Based on the previous studies, we propose the following hypothesis: CHEK2 is involved in the regulation of the effect of chemotherapeutic drugs on human breast cancer cells, and CHEK2 mutations may cause drug resistance to chemotherapy agents in breast cancer cells.…”
Section: Introductionmentioning
confidence: 82%
“…Subsequently, CHEK2 WT (wild-type CHEK2) or CHEK2 Y390C (CHEK2 Y390C mutation) was re-expressed in the CHEK2 knockdown MDA-MB-231 cells as previously described [ 7 ]. Cells transfected with vector control were used as the control group.…”
Section: Methodsmentioning
confidence: 99%